Direct hydrogenation of CO2 to liquid hydrocarbons over K/Fe-C catalysts: Effect of porous carbon matrix and K modification - Chen, Xixi; Gao, Ruxing; Wang, Qiang; Hu, Kehao; Wang, Fenfen; Deng, Chao; Xu, Lujing; Zhang, Chundong; Jun, Ki Won; Ki Kim, Seok; Zhao, Tiansheng; Wan, Hui; et al. (Fuel, 2024)
Direct hydrogenation of CO2 to liquid hydrocarbons via modified Fischer-Tropsch synthesis represents an appealing and sustainable route for efficient CO2 utilization. However, the selective production of liquid hydrocarbons remains a significant challenge. In this work, we designed a series of carbon-coated K/Fe-C catalysts with various K loadings (ranging from 0 to 8 wt%) that enhance C5+ hydrocarbon selectivity during CO2 hydrogenation. It is found that the 4 K/Fe-C catalyst exhibits the highest C5+ selectivity of 54.78 % at CO2 conversion of 32.40 % and good stability within 100 h time-on-stream. This is attributed to the high dispersion of the Fe nanoparticles and the confinement effect of porous carbon matrix on the aggregation of Fe nanoparticles, resulting in high catalytic activity and selectivity. Meanwhile, the well dispersed K on the porous carbon matrix can reduce the particle size of Fe nanoparticles and promote the production of iron carbide active species for CO2-FTS, thus facilitating the selective formation of C5+ hydrocarbons. Moreover, we also discussed a possible reaction mechanism for the direct hydrogenation of CO2 to C5+ hydrocarbons over the K/Fe-C catalysts. This study provides deep insights into the design of efficient Fe-C catalysts for converting CO2 to liquid hydrocarbons.
Keywords: CO2 hydrogenation; Fe-based catalyst; Fischer-Tropsch synthesis; Long-chain hydrocarbons; Metal-organic frameworks